Speaking extra : a resource book of multi-level skills activities. - Gammidge, Mick, ....- (Cambridge : University Press, 2005)
This lively resource book encourages students to expand their speaking skills using role play, problem solving, puzzles, games, interviews, storytelling and discussion. Many of the speaking activities are supported by the accompanying audio CD and the recording script section at the back of the resource book.
Keywords: Engels -- Taalgebruik; Spreekkunst